2018
DOI: 10.1128/msphere.00548-18
|View full text |Cite
|
Sign up to set email alerts
|

Fh15 Blocks the Lipopolysaccharide-Induced Cytokine Storm While Modulating Peritoneal Macrophage Migration and CD38 Expression within Spleen Macrophages in a Mouse Model of Septic Shock

Abstract: Sepsis is a potentially life-threatening complication of an infection. Sepsis is mostly the consequence of systemic bacterial infections leading to exacerbated activation of immune cells by bacterial products, resulting in enhanced release of inflammatory mediators. Lipopolysaccharide (LPS), the major component of the outer membrane of Gram-negative bacteria, is a critical factor in the pathogenesis of sepsis, which is sensed by Toll-like receptor 4 (TLR4). The scientific community highly pursues the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 43 publications
8
21
1
Order By: Relevance
“…Specifically, the helminth parasite Fasciola hepatica has shown immunomodulatory properties, and several molecules from this parasite have been described as potent immunomodulators [7]. Derivatives of these molecules in their synthetic, safe formats have given rise to promising results; for example, a 68 mer peptide of helminth defense molecule (HDM) has been shown to inhibit inflammation and airway hyper-reactivity in murine experimental asthma [8], and the fatty-acid-binding recombinant protein Fh15 blocked the lipopolysaccharide (LPS)-induced cytokine storm in a murine model [9]. As a result, recombinant safeto-use forms of the above-mentioned molecules are available.…”
Section: Severe Cases Of Coronavirus Disease 2019 (Covid-19)mentioning
confidence: 99%
“…Specifically, the helminth parasite Fasciola hepatica has shown immunomodulatory properties, and several molecules from this parasite have been described as potent immunomodulators [7]. Derivatives of these molecules in their synthetic, safe formats have given rise to promising results; for example, a 68 mer peptide of helminth defense molecule (HDM) has been shown to inhibit inflammation and airway hyper-reactivity in murine experimental asthma [8], and the fatty-acid-binding recombinant protein Fh15 blocked the lipopolysaccharide (LPS)-induced cytokine storm in a murine model [9]. As a result, recombinant safeto-use forms of the above-mentioned molecules are available.…”
Section: Severe Cases Of Coronavirus Disease 2019 (Covid-19)mentioning
confidence: 99%
“…Peripheral blood of severe COVID-19 patients has also shown a high level of cytokine storm (Wu and Yang, 2020 ). Keeping in mind the ability of lipopolysaccharide (LPS) to cause sepsis and triggers an uncontrolled systemic inflammatory response in murine macrophage cells (Ramos-Benitez et al., 2018 ), we treated macrophage cells with LPS (1 µg/ml) in the presence and absence of LDN (5 µM). The dose of LDN chosen is non-toxic ( Figure S2 ) as found in cell viability using MTT (4,5-dimethylthiazol-2-yl-2,5-diphenyltetrazolium bromide) assay following the standard protocol (Dogra et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Peripheral blood of severe COVID-19 patients has also shown a high level of cytokine storm 14 . Keeping in mind the ability of lipopolysaccharide (LPS) to cause sepsis and triggers an uncontrolled systemic inflammatory response in murine macrophage cells 15 , we treated macrophage cells with LPS (1μg/ml) in presence and absence of LDN (5 μM). Results demonstrated that LPS treatment significantly induced expression on pro-inflammatory cytokines (IL-1β, IL-6and TNF-a) whereas, LDN significantly inhibited LPS expression of IL-1β, IL-6and TNF-a in macrophage cells (Fig.…”
Section: Resultsmentioning
confidence: 99%